2000
DOI: 10.1063/1.1315600
|View full text |Cite
|
Sign up to set email alerts
|

Chemically selective adsorption of molecular oxygen on GaAs(100)c(2×8)

Abstract: Articles you may be interested inOxygen adsorption-induced nanostructures and island formation on Cu{100}: Bridging the gap between the formation of surface confined oxygen chemisorption layer and oxide formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…It has been reported for GaAs that oxygen will bond preferentially to Ga atoms that are below As dimers, with subsequent oxidation of nearby Ga dimers, and the formation of As clusters. 19 In each of the EELS profiles, we can see a slight increase in the As and In signals in the In 0.53 Ga 0.47 As substrate near the HfO 2 / In 0.53 Ga 0.47 As interface, with an increase in the Ga signal overlapping the oxygen at the interface. This is consistent with the proposed model for GaAs oxidation.…”
Section: Resultsmentioning
confidence: 96%
“…It has been reported for GaAs that oxygen will bond preferentially to Ga atoms that are below As dimers, with subsequent oxidation of nearby Ga dimers, and the formation of As clusters. 19 In each of the EELS profiles, we can see a slight increase in the As and In signals in the In 0.53 Ga 0.47 As substrate near the HfO 2 / In 0.53 Ga 0.47 As interface, with an increase in the Ga signal overlapping the oxygen at the interface. This is consistent with the proposed model for GaAs oxidation.…”
Section: Resultsmentioning
confidence: 96%
“…Growth is carried out at a temperature that is 40-50 1C above the transition temperature T t with the chamber pressure at around 10 À 5 Torr limited by oxygen from the source decomposition. Although the (2 Â 4) reconstructed GaAs surface is exposed to a high partial pressure of oxygen, the sticking coefficient of O 2 on GaAs is about six orders of magnitude lower than that of Ga 2 O at room temperature [26]. Under these conditions the growth rate is approximately 1Å/min for bulk Ga 2 O 3 .…”
Section: Methodsmentioning
confidence: 98%
“…Furthermore we found that the sign of the 4 eV signal relative to the 2.6 eV signal, was always the same, indicating that the anisotropy of the c(4 · 4)/d(4 · 4) surface must also influence the anisotropy of the resulting oxide. Thus since the only anisotropic structure present in the system is at the surface, we suggest that the resulting anisotropic oxide is influenced by the structure of the surface, which constrains the adsorption and reaction of the oxygen as has been seen in other studies performed under vacuum [8][9][10].…”
Section: Resultsmentioning
confidence: 80%
“…Previously we have shown that these trends are characteristic of a pseudo first-order decay behaviour [26]. Other studies of the reactivity of oxygen with GaAs have shown that the reaction tends to occur at the Ga-As bonds while As forms elemental clusters form on the surface [5][6][7][8][9][10][11] so it may be the case that the loss of the 2.6 eV signal is related to As surface migration and cluster formation rather than direct reaction of the As-As dimers with oxygen, such has been seen in other studies where the 2.6 eV signal has been made to disappear [18,20]. However direct confirmation of a mechanism involving cluster formation in preference to As-As dimer destruction would be particularly challenging for surfaces as reactive as these, held under atmospheric pressure conditions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation